The Right of Silence and Privilege against Self-Incrimination in Criminal Proceedings: An Appraisal of the Ethiopian Legal Framework - Gebre, Wendmagegn Fantaye (Bahir Dar University Journal of Law, 2022)
Individuals can, theoretically, lead their lives without ever having to declare any kind of information or testimony to any other person or institution. However, there are a number of occasions whereby they may be lawfully required to provide information or testimony to a state. One such situation is during a criminal proceeding. In view of that, anyone suspected or accused of crime may be confronted with state authorities and thus may be questioned as to an alleged crime. Yet, persons suspected or accused of an alleged crime are entitled to certain minimum basic guarantees during criminal proceedings. Two such guarantees are the right of silence and the privilege against self-incrimination. The precise reach of the right to silence and the privilege against selfincrimination in criminal proceedings is both unclear and thorny. This article examines what they mean according to international standards. It primarily appraises the Ethiopian legal framework relating to such rights in light of the experiences of different countries of various legal traditions and some major international and regional human rights instruments.